Low-density Lipoprotein Improves Motility and Plasma Membrane Integrity of Cryopreserved Canine Epididymal Spermatozoa - Prapaiwan, N (Asian-Australasian journal of animal sciences, 2016)
Cryopreservation of caudal epididymal spermatozoa is an effective technique to conserve genetic potentials of superior dogs when it is not possible to collect ejaculated spermatozoa. Although hen egg yolk is commonly supplemented into the semen extender, active substances within the egg yolk which protect sperm against cryoinjury remain to be discovered. Among its compositions, low-density lipoprotein (LDL) has been reported to have a cryoprotective property for sperm cryopreservation. However, the effects of LDL on dog epididymal spermatozoa during cryopreservation have not yet been investigated. This study aimed to investigate the effects of LDL on epididymal spermatozoa quality following cryopreservation and thawing. After routine castration of 12 dogs, caudal epididymides from individuals were separated from the testes and cut into a few pieces in a Tris-buffer. Spermatozoa recovered from each sample were examined at once for sperm quality and divided into six groups of extender: no LDL, 20% egg yolk, 4%, 8%, 16%, and 24% LDL, before cryopreservation. The sperm aliquots were then equilibrated and conventionally frozen. After thawing, sperm motility, morphology, plasma membrane integrity, and acrosome integrity were evaluated. The results revealed that 4% LDL and 20% egg yolk yielded significantly higher sperm motility (57.69% and 52.69%, respectively, p<0.05) than other LDLs. In addition, 4% LDL yielded the significantly highest plasma membrane integrity (70.54%, p<0.05). In conclusion, the supplementation of 4% LDL in Tris-glucose extender could be applied for cryopreservation of canine epididymal spermatozoa